Optimalization of Spare Part Inventory Management: Case Study at PT XYZ - Vanessa Christine Siregar; Nureni Wijayati (Green Publisher Indonesia, 2026)
The purpose of this study is to evaluate the causes behind PT XYZ’s inadequate spare parts inventory management. This study uses a case study with a problem diagnosis approach as its methodology. Interviews were used to obtain the research data. Five decision-making phases are used as a conceptual framework for the analysis of the interview data. Industrial managers are guided by these five steps in managing actual spare parts in their organizations. The findings from this study reveal that the company has not fully optimized each stage, resulting in continued inefficiencies in inventory management. By identifying these issues, the suggested improvements are tailored to the specific challenges faced at each stage, making them applicable for implementation in inventory management to achieve greater effectiveness. This study concludes that PT XYZ’s spare parts inventory management inefficiencies stem from weaknesses across all five decision-making stages. The proposed solutions include: (1) implementing a standardized numbering system combining part classification, serial number, and storage location; (2) adopting VED (Vital, Essential, Desirable) classification based on criticality; (3) applying statistical forecasting methods such as lead-time demand analysis to determine reorder points and safety stock; (4) developing data-driven stock management policies aligned with part classification; and (5) establishing regular policy evaluation through simulations and cross-divisional discussions